A Quality Improvement Initiative Using a Novel Travel Survey to Promote Patient‐Centered Counseling. Issue 4 (21st May 2013) - Mackaness, Craig A.; Osborne, Allison; Verma, Deepti; Templer, Suzanne; Weiss, Michael J.; Knouse, Mark C.
Abstract : Background: We sought to evaluate and provide better itinerary‐specific care to precounseled travelers and to assess diseases occurring while traveling abroad by surveying a community population. An additional quality improvement initiative was to expand our post‐travel survey to be a more valuable tool in gathering high‐quality quantitative data. Methods: From de‐identified data collected via post‐travel surveys, we identified a cohort of 525 patients for a retrospective observational analysis. We analyzed illness encountered while abroad, medication use, and whether a physician was consulted. We also examined itinerary variables, including continents and countries visited. Results: The 525 post‐travel surveys collected showed that the majority of respondents traveled to Asia (31%) or Africa (30%). The mean number of travel days was 21.3 (median, 14). Univariate analysis demonstrated a statistically significant increase of risk for general illness when comparing travel duration of less than 14 days to greater than 14 days (11.3% vs 27.7%, p < 0.001). Duration of travel was also significant with regard to development of traveler's diarrhea (TD) ( p = 0.0015). Destination of travel and development of traveler's diarrhea trended toward significance. Serious illness requiring a physician visit was infrequent, as were vaccine‐related complications. Conclusions: Despite pre‐travel counseling, traveler's diarrhea was the most common illness in our cohort; expanded prevention strategies will be necessary to lower the impact that diarrheal illness has on generally healthy travelers. Overall rates of illness did not vary by destination; however, there was a strong association between duration of travel and likelihood of illness. To further identify specific variables contributing to travel‐related disease, including patient co‐morbidities, reason for travel, and accommodations, the post‐travel survey has been modified and expanded. A limitation of this study was the low survey response rate (18%); to improve the return rate, we plan to implement supplemental modalities including email and a web‐based database.